ANALISIS FRAMING CHANNEL YOUTUBE DR. RICHARD LEE TENTANG KEAMANAN DAN STRATEGI PEMASARAN PRODUK HN - Mega Lusi Sartika; Sakti Ritonga; Muhammad Jailani (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to explain what safety and marketing strategies should be carried out by sellers of hn products. This research was conducted using a more advanced qualitative approach which is the level of framing analysis. More specifically, the researcher uses the framing analysis method with Robert N. Etman's analytical model. The results of this study show that from a series of videos on Dr.'s YouTube channel. Richard Lee emphasized that the marketing of unsafe cosmetics is still circulating freely among the public. Dr. Richard Lee tries to educate women, so they don't get stuck using unsafe products. Dr. Richard Lee considers HN products to be products that contain harmful substances for facial skin because they are indicated to have hydroquinone and mercury ingredients.